KEEFEKTIFAN MACROMEDIA FLASH TERHADAP HASIL BELAJAR IPA SISWA KELAS III SD NEGERI 06 LARANGAN - Widiyawati, Indri (Universitas Slamet Riyadi, 2018)
The purpose of this study is to determine the effectiveness of the use of Macromedia Flash to improve the learning outcomes of science grade 3 SDN 06 Larangan. The method used is Pre-Experimental Designs (non-campaign type One Pretest-Posttest Design Group. The results showed the posttest results have a higher average of 75.17 and the results of the pretest have an average value of 51.33 so that the t test value is 9365 with t table that is 2.042, it can be concluded that t count> t table means that H1 is accepted so that it can be said that Macromedia Flash learning media is effective or influences the learning outcomes of science students of SD Negeri 06 Larangan